IL‐22 and IL‐22 binding protein (IL‐22BP) regulate fibrosis and cirrhosis in hepatitis C virus and schistosome infections. Issue 4 (10th March 2015) - Sertorio, Mathieu; Hou, Xunya; Carmo, Rodrigo F.; Dessein, Hélia; Cabantous, Sandrine; Abdelwahed, Mohammed; Romano, Audrey; Albuquerque, Fernanda; Vasconcelos, Luydson; Carmo, Theomira; Li, Jun; Varoquaux, Arthur; et al.
Abstract : Interleukin (IL)‐22 acts on epithelia, hepatocytes, and pancreatic cells and stimulates innate immunity, tissue protection, and repair. IL‐22 may also cause inflammation and abnormal cell proliferation. The binding of IL‐22 to its receptor is competed by IL‐22 binding protein (IL‐22BP), which may limit the deleterious effects of IL‐22. The role of IL‐22 and IL‐22BP in chronic liver diseases is unknown. We addressed this question in individuals chronically infected with schistosomes or hepatitis C virus (HCV). We first demonstrate that schistosome eggs stimulate production of IL‐22 transcripts and inhibit accumulation of IL22‐BP transcripts in schistosome‐infected mice, and that schistosome eggs selectively stimulate production of IL‐22 in cultures of blood leukocytes from individuals chronically infected with Schistosoma japonicum . High IL‐22 levels in cultures correlated with protection against hepatic fibrosis and portal hypertension. To test further the implication of IL‐22/IL‐22BP in hepatic disease, we analyzed common genetic variants of IL22RA2, which encodes IL‐22BP, and found that the genotypes, AA, GG of rs6570136 ( P = 0.003; odds ratio [OR] = 2), and CC, TT of rs2064501 ( P = 0.01; OR = 2), were associated with severe fibrosis in Chinese infected with S. japonicum . We confirmed this result in Sudanese (rs6570136 GG [ P = 0.0007; OR = 8.2], rs2064501 TT [ P = 0.02; OR = 3.1]), and Brazilians (rs6570136 GG [ P = 0.003; OR = 26], rs2064501 TC, TT ( P = 0.03; OR = 11]) infected with S. mansoni . The aggravating genotypes were associated with high IL22RA2 transcripts levels. Furthermore, these same variants were also associated with HCV‐induced fibrosis and cirrhosis (rs6570136 GG, GA [ P = 0.007; OR = 1.7], rs2064501 TT, TC ( P = 0.004; OR = 2.4]). Conclusions : These results provide strong evidence that IL‐22 protects against and IL‐22BP aggravates liver fibrosis and cirrhosis in humans with chronic liver infections. Thus, pharmacological modulation of IL‐22 BP may be an effective strategy to limit cirrhosis. (Hepatology 2015;61:1321–1331)